Effect of carbon dioxide versus room air insufflation on post-colonoscopic pain: A prospective, randomized, controlled study - Gündüz, Feyza; Kani, Haluk Tarık; Chang, Shannon; Akdeniz, Esra; Eren, Fatih; Yılmaz, Yusuf; Özen Alahdab, Yeşim (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Room air (RA) and carbon dioxide (CO2) are widely used to insufflate the colon to examine the mucosa in colonoscopy. Pain, discomfort, and bloating can be seen during and after colonoscopy secondary to bowel distention. This study aimed to investigate the effect of CO2 on post-procedure pain sensation (PPPS) in comparison with RA.Materials and Methods: Patients were randomly assigned to the RA and CO2 insufflation groups in a 1:1 ratio. The visual analog scale (VAS) was used to measure the pain before and after the colonoscopy. VAS score of 0 was accepted as the absence of pain and above 0 was accepted as the presence of pain. The primary outcome was to investigate the effect of CO2 insufflation on PPPS. Secondary outcomes were to investigate the other contributing factors affecting PPPS and the effect of CO2 on PPPS in patients with inflammatory bowel disease (IBD).Results: A total of 204 patients were enrolled in the study. No significant difference in PPPS was seen between the 2 groups at any point in time after the colonoscopy. Furthermore, there was no significant difference in pain sensation between the CO2 and RA groups in patients with IBD. When we investigated the other contributing factors to pain sensation, body-mass index (BMI) was found to be significant at 30 minutes and BMI and colonoscopy time were found to be significant at 6 hours afterwards. Conclusion: We found no favorable effect of CO2 insufflation on PPPS in colonoscopy, including in patients with IBD.